Method for improving stability and luminescence performance of perovskite nano-particles and stable perovskite nano-particles obtained by using method

By performing electron beam treatment on perovskite nanoparticles, a semi-amorphous carbon structure is formed, which solves the problem of insufficient stability and luminescence performance, significantly improves the photothermal stability and luminescence performance of the nanoparticles, and is suitable for micro-nano applications. device applications.

CN119331596APending Publication Date: 2025-01-21PEKING UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411232487.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-26
Filing Date
2024-09-04
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Perovskite nanoparticles have poor stability and are prone to spontaneous aggregation and growth under external conditions such as light and heating, affecting their emission characteristics and device efficiency.

Method used

Filterrior nanoparticles covered by the solution synthetic surface ligand, and dispersed it to the solid matrix, and then use the electronic beam of the electronic microscope to the surface ligand of the nanoparticles to form a semi -fixed carbon structure to fix it to fix Nano particles.

Benefits of technology

Effectively prevent the agglomeration and growth between nanoparticles, increase its light thermal stability, and improve the lighting performance, and it is suitable for the application of micro -nano components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331596A_ABST
    Figure CN119331596A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving stability and luminescence performance of perovskite nanoparticles and stable perovskite nanoparticles obtained by the method. The method comprises the following steps: step S1, synthesizing surface ligand coated perovskite nanoparticles by using a solution method; step S2, dispersing the synthesized perovskite nanoparticles into a solid matrix; and S3, carrying out post-treatment on the surface ligands of the perovskite nanoparticles by using electron beams of an electron microscope. According to the method, aggregation and growth of nano-particles can be effectively prevented even under the conditions of illumination heating and the like, the photo-thermal stability of the nano-particles is improved, the luminescence performance can be improved, and the nano-particles can be applied to micro-nano devices with better performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal halide perovskite nanoparticles, in particular to a method for improving the stability and luminescent performance of perovskite nanoparticles and stable perovskite nanoparticles obtained by the method. Background Art

[0002] In recent years, metal halide perovskite nanoparticles (LHP NPs) have been widely studied and used in various optoelectronic applications such as color conversion layers, photodetectors, solar cells and light-emitting diodes. This is due to their adjustable band gap, high charge mobility, long carrier lifetime, excellent fluorescence quantum efficiency and simple and economical manufacturing process. LHP NPs are composed of inorganic cores and surface ligands, in which the ligands act as a protective barrier and play an important role in preventing the inorganic core from fusion and maintaining the stability of the nanostructure. However, due to the highly dynamic binding interaction between the ligands and the surface ions, the ability of the ligands to attach to the surface of NPs is relatively weak. This leads to the relatively poor stability of LHP NPs, which are easy to spontaneously aggregate and grow, adversely affecting their emission characteristics and significantly reducing the efficiency of the device. This is especially obvious under the stimulation of external conditions such as light and heating. Whether LHP NPs are used as the active layer of solar cells, the active layer in LEDs or as color conversion layers, they are inevitably affected by light and heat. This seriously hinders their practical application. Therefore, it is particularly urgent to develop a solution to improve the photothermal stability of LHP NPs and maintain or even improve the optical properties.

[0003] At present, the main strategies for improving the stability of LHP NPs can be divided into surface ligand exchange, surface coating and encapsulation. It is reported that the introduction of zwitterionic ligands through a simple solution-phase ligand exchange method can not only obtain high-concentration high-quality colloidal nanoparticles, but also significantly improve the stability of LHP NPs in the environment. However, this ligand exchange method may affect the morphology of the product, resulting in uneven size distribution. The surface coating method is to cover the surface of LHP NPs with a protective layer, including inorganic substances such as silica, and organic polymers such as polymethyl methacrylate (PMMA). However, this method generally has problems such as harsh reaction conditions and complex processes. In comparison, electron beam lithography technology has obvious advantages. On the one hand, the irradiation dose is controllable, and on the other hand, the irradiation area is controllable-especially the electron beam processing technology based on electron microscopy has a high spatial resolution and can be precisely controlled at the micron or even nanometer level. This in-situ processing method can achieve the improvement of the stability of nanoparticles in LHP NPs devices, which is particularly suitable for micro-nano device applications.

[0004] Although there are many solutions to improve the photothermal stability of LHP NPs, they either have harsh reaction conditions and complex processes, or may have adverse effects on the morphology and size distribution of the products. Since the processing range cannot be directly and accurately controlled, especially in the micro-nano space range, its application in micro-nano devices is greatly limited.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned technical deficiencies and provide a method for improving the stability and luminescence performance of perovskite nanoparticles and perovskite nanoparticles dispersed on a solid matrix, which can effectively prevent the aggregation growth between nanoparticles even under conditions such as light heating, increase their photothermal stability, and improve luminescence performance, which is helpful for application in micro-nano devices with better performance.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0008] According to one aspect of the present invention, there is provided a method for improving the stability and luminescence performance of perovskite nanoparticles, comprising the following steps:

[0009] Step S1, synthesizing surface ligand-coated perovskite nanoparticles using a solution method;

[0010] Step S2, dispersing the synthesized perovskite nanoparticles into a solid matrix;

[0011] Step S3, using the electron beam of an electron microscope to post-treat the ligands on the surface of the perovskite nanoparticles.

[0012] Furthermore, in step S1, the perovskite nanoparticles are synthesized in combination with a hot injection method.

[0013] Furthermore, the surface ligands include oleylamine and oleic acid.

[0014] Furthermore, the perovskite nanoparticles are metal halide nanomaterials of APbX3 structure, wherein A is Cs + , X is Br - .

[0015] Furthermore, the electron beam light source comes from a transmission electron microscope with an energy of 80-200 kV, or comes from a scanning electron microscope with an energy of 1-30 kV.

[0016] Furthermore, the solid substrate includes a carbon film and a silicon wafer.

[0017] Furthermore, the step S1 specifically includes:

[0018] Cesium carbonate, octadecene and oleic acid are added to a container, and the resulting mixture is heated under a nitrogen environment until all the cesium carbonate is completely dissolved. In another container, lead bromide is mixed with octadecene, oleylamine and oleic acid, and the resulting solution is degassed with nitrogen under heating, then heated, and the cesium oleate precursor solution is quickly injected into the mixture. After the reaction is completed, it is cooled in an ice water bath, centrifuged, the supernatant is discarded, the sample is redispersed in cyclohexane and purified with ethyl acetate, and finally the purified nanocrystals are redispersed in cyclohexane.

[0019] According to another aspect of the present invention, there is also provided a stable perovskite nanoparticle dispersed on a solid matrix, which is prepared by the above-mentioned method for improving the stability and luminescence performance of the perovskite nanoparticle.

[0020] Compared with the existing technology, the advantages of the present invention include: under continuous electron beam irradiation, oleylamine and oleic acid molecules undergo continuous C-C bond rupture and hydrogen atom detachment, forming C=C double bonds to convert saturated hydrocarbons into unsaturated hydrocarbons. This conversion produces a graphene-like semi-amorphous carbon structure that can fix the nanoparticles in their original positions. The fixed nanoparticles basically do not move, so even under conditions such as light heating, the aggregation growth between nanoparticles can be effectively prevented, thereby increasing their photothermal stability. More importantly, electron beam irradiation can not only increase stability, but also effectively increase luminescence performance, which is of great significance in the application of micro-nano devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Transmission electron microscopy (TEM) image (a) and the corresponding fast Fourier transform (FFT) image (b) of the original CsPbBr3 nanoparticles synthesized by hot injection method;

[0022] Figure 2 The morphology of the original sample and the sample after heating treatment;

[0023] Figure 3 Schematic diagram of the electron beam treatment process;

[0024] Figure 4 To analyze the effect of electron beam treatment on the thermal stability of CsPbBr3 nanoparticles, the effects of different electron beam irradiation doses were compared by heating at 95°C for 40 minutes.

[0025] Figure 5 Fluorescence emission spectra of untreated and electron beam irradiated CsPbBr3 nanoparticles. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present application.

[0027] The embodiment of the present invention provides a method for improving the stability and luminescence performance of perovskite nanoparticles, comprising the following steps:

[0028] Step S1, synthesizing surface ligand-coated perovskite nanoparticles using a solution method;

[0029] Step S2, dispersing the synthesized perovskite nanoparticles into a solid matrix;

[0030] Step S3, using the electron beam of an electron microscope to post-treat the ligands on the surface of the perovskite nanoparticles.

[0031] Organic surface ligands are present during the synthesis of perovskite nanoparticles, usually oleylamine, oleic acid, etc., which have -NH2 and -COOH groups and unsaturated C=C.

[0032] Electron beam processing involves extremely high energy (>1kV) and high vacuum conditions (<10 -5 Pa), which can easily destroy the surface ligands. Under continuous electron beam irradiation, oleylamine and oleic acid molecules undergo continuous CC bond breakage and hydrogen atom detachment, forming C=C double bonds to convert saturated hydrocarbons into unsaturated hydrocarbons. This conversion produces a graphene-like semi-amorphous carbon structure that can firmly fix the nanoparticles in their original position.

[0033] In addition, the luminescence performance can be adjusted by adjusting the electron beam irradiation dose.

[0034] As an example, perovskite nanoparticles were prepared as follows: 2.4 mmol of cesium carbonate, 36 mL of octadecene, and 4 mL of oleic acid were added to a 50 mL three-necked flask. The mixture was heated at 120 °C under nitrogen for 1 hour and then heated at 150 °C until all the cesium carbonate was completely dissolved. In another round-bottomed three-necked flask, 0.4 mmol of lead bromide was mixed with 10 mL of octadecene, 1 mL of oleylamine, and 1 mL of oleic acid. The solution was degassed with nitrogen at 120 °C for 1 hour. The temperature was then raised to 210 °C, and 1 mL of cesium oleate precursor solution was quickly injected into the mixture. After annealing for 10 seconds, it was cooled in an ice-water bath. The solution was centrifuged at 5000 rpm for 3 minutes. Then, the supernatant was discarded, and the sample was redispersed in cyclohexane and purified with ethyl acetate. Finally, the purified nanocrystals were redispersed in cyclohexane.

[0035] In this embodiment, CsPbBr3 nanoparticles were synthesized by hot injection method, and the surface ligands were long-chain oleic acid and oleylamine. The morphology and structure of the nanoparticles were characterized by transmission electron microscopy (TEM). Figure 1 TEM image of synthesized CsPbBr3 nanoparticles. Figure 1 It can be seen that the size distribution of the synthesized nanoparticles is relatively uniform, with an average size of about 18 nanometers and regular morphology. From the corresponding fast Fourier transform (FFT) ( Figure 1 (b)) can determine that the structure of the sample is an orthorhombic phase.

[0036] Due to the ionic nature of their structure, CsPbBr3 nanoparticles are prone to aggregation and growth, especially under external conditions such as heating and light. Figure 2 The morphology of the initial sample and the sample heated at 95°C for 40 minutes in vacuum is shown in the figure. It can be clearly seen from the figure that the size increase and morphology change caused by heating. This causes the nanoparticles to lose their nanostructure characteristics, which seriously affects their application.

[0037] Based on this, we investigated the effect of electron beam treatment on thermal stability based on scanning electron microscopy. Figure 3 Schematic diagram of electron beam irradiation treatment. High-energy electron beam acts on the surface ligands and internal inorganic cores of CsPbBr3 nanoparticles. The acceleration voltage used is 20kV. The total irradiation dose is controlled by controlling the size of the irradiation area and the length of the irradiation time.

[0038] Next, we evaluate the effectiveness of the treatment. Figure 4TEM images of samples treated with different electron beam irradiation doses after 40 minutes of vacuum heating at 95°C. It can be seen that even low-dose electron beam irradiation increases the size and morphology stability of the particles, and some particles no longer grow under heating conditions. With the increase of electron beam irradiation dose, the particle growth caused by heating is significantly inhibited, especially when the dose reaches 2800 μC cm -2 When the dose was increased to 11200 μC cm -2 The particles do not grow at all.

[0039] At the same time, we also study the effect of electron beam irradiation on the luminescence properties. Figure 5 The fluorescence emission spectra of CsPbBr3 nanoparticles without treatment and after electron beam irradiation treatment are shown in Figure 2. We found that after irradiation treatment, the luminescence performance of CsPbBr3 nanoparticles was significantly enhanced, and the size stability of CsPbBr3 nanoparticles became obvious with the increase of irradiation dose. This result shows that after electron beam irradiation, not only the stability can be increased, but also the luminescence performance can be effectively increased, which is of great significance for the practical application of materials such as CsPbBr3 nanoparticles.

[0040] The above is only a preferred embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.

Claims

1. A method for improving the stability and luminescence performance of perovskite nanoparticles, characterized in that: The steps include: Step S1, synthesizing surface ligand-coated perovskite nanoparticles using a solution method; Step S2, dispersing the synthesized perovskite nanoparticles into a solid matrix; Step S3, using the electron beam of an electron microscope to post-treat the ligands on the surface of the perovskite nanoparticles.

2. The method for improving the stability and luminescence performance of perovskite nanoparticles according to claim 1, characterized in that: In the step S1, the perovskite nanoparticles are synthesized in combination with the hot injection method.

3. The method for improving the stability and luminescence performance of perovskite nanoparticles according to claim 2, characterized in that: The surface ligands include oleylamine and oleic acid.

4. The method for improving the stability and luminescence performance of perovskite nanoparticles according to claim 1, characterized in that: The perovskite nanoparticles are metal halide nanomaterials with APbX3 structure, wherein A is Cs + , X is Br - .

5. The method for improving the stability and luminescence performance of perovskite nanoparticles according to claim 1, characterized in that: The electron beam light source is derived from a transmission electron microscope with an energy of 80-200 kV, or is derived from a scanning electron microscope with an energy of 1-30 kV.

6. The method for improving the stability and luminescence performance of perovskite nanoparticles according to claim 1, characterized in that: The solid substrate includes a carbon film and a silicon wafer.

7. The method for improving the stability and luminescence performance of perovskite nanoparticles according to any one of claims 1 to 6, characterized in that: The step S1 specifically includes: Cesium carbonate, octadecene and oleic acid are added to a container, and the resulting mixture is heated under a nitrogen environment until all the cesium carbonate is completely dissolved. In another container, lead bromide is mixed with octadecene, oleylamine and oleic acid, and the resulting solution is degassed with nitrogen under heating, then heated, and the cesium oleate precursor solution is quickly injected into the mixture. After the reaction is completed, it is cooled in an ice water bath, centrifuged, the supernatant is discarded, the sample is redispersed in cyclohexane and purified with ethyl acetate, and finally the purified nanocrystals are redispersed in cyclohexane.

8. A stable perovskite nanoparticle dispersed on a solid matrix, characterized in that: The nanostructured perovskite is prepared by the method for improving the stability and luminescence performance of perovskite nanoparticles as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of novel perovskite quantum dot

    CN107267143A

  • Method for electron beam irradiation patterning of perovskite nanocrystals based on organic ligands

    CN116243559A

  • Preparation method of high-stability CsPbBr (I) 3 quantum dot and wide-color-gamut backlight device

    CN116709872A

  • CsPbBr3 perovskite quantum dot with core-shell structure as well as synthesis method and application of CsPbBr3 perovskite quantum dot

    CN116731703A

  • Perovskite quantum dot surface defect removal method and microscopic scale image acquisition method

    CN117110328A